The The Effectiveness of Podcast on You Tube as a Learning Media in Improving Students' Listening Skills - Kaunain, Safitri Nuril; Hasbullah, Hasbullah; Rahman, Abd. Rahman (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The aim of this study was to evaluate the effective of podcasts as a learning media to improve students' English listening skills in class XII of Senior High School (SMA) Negeri 2 Sorong Regency, Southwest Papua, Indonesia. The study was conducted in the academic year 2023/2024 by using a mixed method for the sequential explanatory design. Listening tests, interviews, and observations were utilized to collect data. The results were analyzed using a paired t-test and qualitative analysis. Quantitative findings indicated a significant improvement in students' listening skills, with the average score increasing from 53.31 in the pre-test to 82.53 in the post-test. It showed an average improvement of 29.22 points. The paired t-test results with a p-value of 0.000, confirmed a statistically significant difference between pre-test and post-test scores which indicate the effectiveness of podcast intervention. The correlation coefficient of 0.882 highlighted a strong positive relationship between the podcast in use and students’ improvement of listening abilities. The interview results also found that most students were interesting and helpful in using podcast for listening skills, especially since they could re-listen to better understand in spoken English. However, some students faced problems such as accents that were difficult to understand or a speaking speed that was too fast. It was recommended to use podcast as an effective media to increase learners’ listening skill achievement and their English ability.